2010
DOI: 10.1007/s12031-010-9410-5
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rat Retinal Ganglion Cell Death by PACAP Following Transient Ischemia Induced by High Intraocular Pressure

Abstract: Glaucoma is a neurodegenerative disease in which increasing intraocular pressure leads to the progressive loss of retinal ganglion cells (RGCs) and blindness. Here, we report a neuroprotective effect of pituitary adenylate cyclase-activating polypeptide (PACAP) against RGC loss induced by high intraocular pressure in the rat. Vehicle or PACAP (1 fM to 1,000 pM) solution was injected into the vitreous body once after induction of a high intraocular pressure (110 mmHg). Seven days later, the number of viable RGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
(20 reference statements)
3
21
0
Order By: Relevance
“…**p<0.01, comparing the NMDA alone and NMDA + PACAP treatment groups in the case of NMDA-induced neuronal injury reflects a simple mechanism, related to direct Ca 2+ influx into the cells via NMDA receptor activity. It has revealed that the bimodal peaks of PACAP neuroprotection has been found in the case of the other glaucoma models, high intraocular pressure, implying these models may be mediated with the complex mechanisms or factors involved in RGC death (Seki et al 2010). It is also possible that the single peak at a nanomolar concentration we observed could be mediated via the cAMP pathway, in line with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…**p<0.01, comparing the NMDA alone and NMDA + PACAP treatment groups in the case of NMDA-induced neuronal injury reflects a simple mechanism, related to direct Ca 2+ influx into the cells via NMDA receptor activity. It has revealed that the bimodal peaks of PACAP neuroprotection has been found in the case of the other glaucoma models, high intraocular pressure, implying these models may be mediated with the complex mechanisms or factors involved in RGC death (Seki et al 2010). It is also possible that the single peak at a nanomolar concentration we observed could be mediated via the cAMP pathway, in line with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…In this model, PACAP exerted a bimodal protective effect with peaks at 10 fM and 10-100 pM. The protective effect was blocked by cAMP antagonist at both high and low protective doses, while a MAP kinase inhibitor only blocked the effects of PACAP at a low dose, suggesting that the protective effects of PACAP are mediated by different signaling at low and high doses [ 79 ].…”
Section: Ischemic Injury In the Retinamentioning
confidence: 84%
“…Seki et al [ 79 ] showed that intravitreal PACAP treatment protected ganglion cells against a different kind of ischemic lesion induced by high intraocular pressure. In this model, PACAP exerted a bimodal protective effect with peaks at 10 fM and 10-100 pM.…”
Section: Ischemic Injury In the Retinamentioning
confidence: 99%
“…5,12,13 Earlier we showed that PACAP1-38 ameliorates the reduction in thickness of different retinal layers as well as the loss of cells in the ganglion cell layer (GCL) in BCCAO-induced injury.…”
Section: Methodsmentioning
confidence: 99%